2015
DOI: 10.1177/0095399715581043
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Ethical Environment to Organizational Performance in Employment at Will States

Abstract: This article highlights the importance of ethical environment in enhancing organizational performance. It is vital that organizations set ethical standards for their employees alongside providing an environment that fosters trust and commitment, provides leadership, and creates a high quality of workforce to improve organizational performance. To study the impact of ethical environment on organizational performance, we employ elements from André de Waal's high-performance organization (HPO) framework. Data for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 82 publications
(180 reference statements)
5
24
0
Order By: Relevance
“…This is in line with the argument that employee satisfaction and organisational performance are correlated and a strong relationship is expected between them (Ostroff, 1992). As empirically supported, motivating work design could positively affect organisational performance (Barrick, et al, 2015;Hijal-Moghrabi, et al, 2015). Moreover, Vermeeren et al (2014) found that job satisfaction positively affects organisational performance.…”
Section: Research Framework and Hypothesessupporting
confidence: 82%
See 1 more Smart Citation
“…This is in line with the argument that employee satisfaction and organisational performance are correlated and a strong relationship is expected between them (Ostroff, 1992). As empirically supported, motivating work design could positively affect organisational performance (Barrick, et al, 2015;Hijal-Moghrabi, et al, 2015). Moreover, Vermeeren et al (2014) found that job satisfaction positively affects organisational performance.…”
Section: Research Framework and Hypothesessupporting
confidence: 82%
“…Barrick, Thurgood, Smith, & Courtright, 2015;Hijal-Moghrabi, Sabharwal, & Berman, 2015;Ostroff, 1992;Zutshi & Sohal, 2004;Vermeeren, Kuipers, & Steijn, 2014). Zutshi and Sohal (2004) found that involving employees in the planning of the environmental management systems benefitted the corporations in enhancing morale building within the corporation, and fulfilling the customer expectations due to considering employees as stakeholders.…”
Section: Research Framework and Hypothesesmentioning
confidence: 99%
“…Based on the above stated justification the researcher intended to employ HRM practices as Independent variables. While on the EC as the moderating variable, previous studies found EC as a strong predictor of organizational performance (Hijal-Moghrabi et al, 2015;Manroop et al, 2014), others prior studies tested EC as moderator on the relationship between job satisfaction and organizational commitment in Asian context (Zehir et al, 2012), African context (Nafei, 2015) result of the previous studies explained positive moderating effect. Based on the above empirical evidences, a proposed research framework for this study illustrating the moderating effect of EC on the relationship between HRM practices and organizational performance is depicted in Figure 1.…”
Section: Proposed Conceptual Modelmentioning
confidence: 92%
“…In other words, EC influences both decision making as well as performances in an organization (Martin & Cullen, 2006). Previous studies found EC as a good predictor on organizational performance (Hijal-Moghrabi et al, 2015;Manroop, Singh, & Ezzedeen, 2014).…”
mentioning
confidence: 96%
See 1 more Smart Citation